The Clinical Outcomes of a Bioinductive Collagen Implant in Bursal-Sided Partial-Thickness Rotator Cuff Tears - Jaesung Yoo; Daehee Lee (Medicina, 2025)
Background and Objectives: Many middle-aged and older individuals experience shoulder pain, often due to partial-thickness rotator cuff tears (PTRCTs). If conservative treatment fails to relieve symptoms in a patient, surgical intervention may be necessary. In such cases, using a bioinductive collagen implant may offer a viable alternative to conventional rotator cuff repair. Most notably, it offers potential advantages, particularly in reducing postoperative pain and promoting faster recovery. Accordingly, this study aims to evaluate the clinical outcomes of treating bursal-sided partial-thickness rotator cuff tears using bioinductive collagen implants alone, without concurrent rotator cuff repair. Materials and Methods: We followed 32 patients who had bursal-sided partial-thickness rotator cuff tears (Ellman grade I or II) and received conservative care for more than six months but continued to experience symptoms. These patients received surgery using bioinductive collagen implants without rotator cuff repair, and we followed up on their postoperative prognosis for at least one year after surgery. For a more accurate contrast, we performed clinical evaluation preoperatively and at 2 weeks, 6 weeks, 3 months, 6 months, and 12 months postoperatively. Visual Analog Scale (VAS), American Shoulder and Elbow Surgeons (ASES) score, Single Assessment Numeric Evaluation (SANE), and Western Ontario Rotator Cuff (WORC) score were used as assessment tools in this study. As for radiological outcomes, magnetic resonance imaging (MRI) and ultrasonography were helpful. This supported our assessment of graft integration and failure. Results: These 32 patients included 13 with Ellman grade I tear and 19 with grade II tear. In both cases, they underwent surgery only using bioinductive collagen implants, and any anchor-based cuff repair was completely excluded. As for VAS (3.8 ± 2.9), certain statistically significant improvements were found starting at 2 weeks postoperatively. On the other hand, the scores of ASES (58.6 ± 20.3), SANE (60.1 ± 23.2), and WORC (59.8 ± 22.4) began to indicate a significant improvement starting at 6 weeks postoperatively (p < 0.001), showing continuous progress. At each final step, we confirmed that there were no cases of graft failure by radiological evaluation and found successful healing indicators, such as much less pain in all patients. Conclusions: The findings of this study provide the clinical evidence that a surgery using bioinductive collagen implant for bursal-sided partial-thickness rotator cuff tears is a highly effective treatment option in patients unresponsive to conservative therapy. Particularly, its practical clinical effectiveness includes facilitating rapid recovery without a significant risk of complications.